Antibacterial potential of a new glucosaminidase from Pediococcus acidilactici ITV26 against Gram-negative and Gram-positive pathogens - Alvarez-Villagomez, Karla G.; Balleza, Daniel; Peña-Montes, Carolina; Fonseca-Barrera, Itzel C.; Mendoza-García, Patricia G. (Frontiers in Microbiology, 2025)
IntroductionPediococcus acidilactici ITV26 is a homofermentative lactic acid bacterium capable of producing pediocins that restrict the proliferation of pathogenic bacteria. However, these bacteria have also been described to produce several peptidoglycan hydrolases (PGH) with great antibacterial potential. These enzymes have been classified as enzybiotics, i.e., proteins capable of degrading cell walls in a highly specific manner to killing pathogens.MethodsThrough differential extraction of protein fractions associated with the membrane of this bacterial strain and in silico analysis, we report the compositional, physicochemical, and biochemical characterization of an enzyme with N-acetylglucosaminidase (NAGase) activity. Additionally, we determined the bactericidal activity of this enzymatic extract against two Gram-positive and two Gram-negative pathogens. We also evaluated ultrastructural changes in sensitive bacteria using scanning electron microscopy (SEM).ResultsThis NAGase activity shows a high specificity against Micrococcus lysodeikticus ATCC 4698 cell walls. The active protein has a molecular mass close to 110 kDa, a sequence of 935 residues, a possible transmembrane fragment close to the N-terminal end, and a profile of high intrinsic flexibility with high hydrophilicity, consistent with a possible topology for a peripheral membrane protein. The enzyme induces significant autolytic activity in P. acidilactici under acidic conditions and is strongly active against Staphylococcus aureus ATCC 6538 and ATCC 25923, Clostridium perfrigens ATCC 12916, Klebsiella pneumoniae ATCC 10031 and Pseudomonas aeruginosa ATCC 25619.DiscussionThis NAGase has great potential as an enzybiotic, as an alternative to the use of conventional antibiotics. Showing little hemolytic activity, this protein has pharmacological potential against multidrug-resistant bacteria. We propose a mechanism of action in which this enzyme hydrolyzes GlcNAc units present in the cell wall of diverse pathogens.